Association of Immunosuppression with DR6 Expression during the Development and Progression of Spontaneous Ovarian Cancer in Laying Hen Model - Sa’Rah McNeal; Pincas Bitterman; Janice M. Bahr; Seby L. Edassery; Jacques S. Abramowicz; Sanjib Basu; Animesh Barua (Journal of Immunology Research)
Ovarian cancer (OVCA) mainly disseminates in the peritoneal cavity. Immune functions are important to prevent OVCA progression and recurrence. The mechanism of immunosuppression, a hallmark of tumor progression, is not well understood. The goal of this study was to determine the immune system’s responses and its suppression during OVCA development and progression in hens. Frequencies of CD8+ T cells and IgY-containing cells and expression of immunosuppressors including IRG1 and DR6 in OVCA at early and late stages in hens were examined. Frequencies of stromal but not the intratumoral CD+8 T cells and IgY-containing cells increased significantly (P<0.01) during OVCA development and progression. Tumor progression was associated with increased expression of IRG1 and DR6 and decreased infiltration of immune cells into the tumor. Frequency of stromal but not intratumoral immune cells increases during OVCA development and progression. Tumor-induced IRG1 and DR6 may prevent immune cells from invading the tumor.